The beneficial role of extracellular reactive oxygen species in apoptosis-induced compensatory proliferation. Issue 1 (2nd January 2017) - Diwanji, Neha; Bergmann, Andreas
ABSTRACT: Apoptosis-induced proliferation (AiP) maintains tissue homeostasis following massive stress-induced cell death. During this phenomenon, dying cells induce proliferation of the surviving cells to compensate for the tissue loss, and thus restore organ size. Along with wound healing and tissue regeneration, AiP also contributes to tumor repopulation following radiation or chemotherapy. There are several models of AiP. Using an "undead" AiP model that causes hyperplastic overgrowth of Drosophila epithelial tissue, we recently demonstrated that extracellular reactive oxygen species (eROS) are produced by undead epithelial cells, and are necessary for inducing AiP and overgrowth. Furthermore, hemocytes, the Drosophila blood cells, are seen adjacent to the undead epithelial tissue, and may secrete the TNF ortholog Eiger that signals through the TNF receptor to active Jun-N-terminal kinase (JNK) in the undead tissue and induce proliferation. We propose that undead epithelial tissue triggers an inflammatory response that resembles recruitment of macrophages to human epithelial tumors, and that these tumor-associated macrophages release signals for proliferation and tumor growth of the epithelium. This Extra View article summarizes these recent findings with a focus on the role of eROS for promoting regeneration and inflammation-induced tumorigenesis.